Effect of Ash, KOH and Millet on the Fermentation of Parkia biglobosa Seeds to Form a Condiment - Pelig-Ba, K.B. (Pakistan Journal of Nutrition, 2009)
Parkia biglobosa seeds were collected from the local market and processed into ‘dawadawa ’, into a local condiment. The process was followed by adding millet, ash and ground potassium hydroxide to determine the effect of these on the fermentation for six days. The food types including, crude protein, fat, carbohydrate, crude fibre, ash and moisture content were determined. Only carbohydrate content was determined by difference. The results showed that pH, crude protein, fat and moisture increased during the period of fermentation, while carbohydrate, crude fibre and ash decreased in content. The mean content of protein was 32.43%, fat (32.43%) and pH (7.68) from the millet treated sample while the others were, carbohydrate (42.73), ash (1.86%) and moisture content (6.53%) from KOH-treated and CF (3.66%) from the raw sample,. The KOH-treated sample produced the least amount of protein and fat but the highest carbohydrate content. In terms of protein content, the rank was millet-treated> ash-treated>raw>KOH-treated. It was found that KOH had a negative effect on the conversion to protein even though it provided an alkaline medium for the process. The effect of millet and ash on fermentation provided the reason for the local people using either but due to relative cost, ash is usually preferred.